On the use of α-shapes for the measurement of 3D bubbles in fluidized beds from Two-Fluid Model simulations - Julián, Ignacio; González, David; Herguido, Javier; Menéndez, Miguel (Jornada de Jóvenes Investigadores del I3A, 2023)
A geometrical technique based on shape construction was employed to reconstruct the simulated domain of 3D bubbles in gas-solid fluidized beds from Two-Fluid Model simulations. The Delaunay triangulation of the cloud of points that represent volume fraction iso-surfaces was filtered using α-shapes, allowing a topologically accurate description of the bubbles.